Vocational Education Teaching the Handicapped in Regular Classes - Council for Exceptional Children, Reston, VA.; Weisgerber, Robert; Council for Exceptional Children, Reston, VA. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
Divided into 7 units, the book provides vocational educational teachers with inservice training on practical knowledge and work skills for working with mainstreamed handicapped students. Unit 1 explores the rights of the handicapped, the capabilities and characteristics of the handicapped, training for competitive employment, shaping the training environment, evaluating the program. Attitudes that can affect success in teaching mainstreamed handicapped students are discussed in unit 2. Units 3,4,5, and 6 deal with individualized instruction for health impaired students, visually handicapped students, mentally retarded students, and students with communications disorders respectively. A plan for action is presented in unit 7, outlining steps for instruction of a specific topic to a specific student. (PHR)
Availability: Council for Exceptional Children, Publication Sales Unit, 1920 Association Drive, Reston, Virginia 22091 ($8.50, Publication No. 179).
Sponsoring Agency: Bureau of Occupational and Adult Education (DHEW/OE), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Handicapped Children; Individualized Instruction; Inservice Teacher Education; Language Handicaps; Mainstreaming; Mental Retardation; Special Health Problems; Visual Impairments; Vocational Education; Books